2021
DOI: 10.28933/ijcr-2021-07-2605
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Shock Due to Acute Myocarditis Following AZD1222 Vaccine Administration: a Case Report

Abstract: Aim: A number of cases of SARS-CoV-2-related myocarditis have been reported since the outbreak of the Covid-19 pandemia, with autoimmune-mediated damage due to molecular mimicry proposed as the virus’ direct mechanism of injury. After commencing with a worldwide mass vaccination program, there have also been reports of myocarditis in the context of Covid-19 immunization. However, myocarditis is still not recognized as a potential side effect of the AZD1222 (ChAdOx1-S recombinant) vaccine administration by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…16 To date, only a few cases of myocarditis following exposure to the AstraZeneca COVID19 vaccine have been published. 17,18 In the current large population study of subjects, who were not vaccinated against SARS-CoV-2, we observed no increase in the incidence of myocarditis or pericarditis from day 10 after positive SARS-CoV-2. Multivariable analysis did show male sex as associated with a higher risk of developing myocarditis or pericarditis, regardless of previous COVID-19 infection.…”
Section: Discussionmentioning
confidence: 55%
“…16 To date, only a few cases of myocarditis following exposure to the AstraZeneca COVID19 vaccine have been published. 17,18 In the current large population study of subjects, who were not vaccinated against SARS-CoV-2, we observed no increase in the incidence of myocarditis or pericarditis from day 10 after positive SARS-CoV-2. Multivariable analysis did show male sex as associated with a higher risk of developing myocarditis or pericarditis, regardless of previous COVID-19 infection.…”
Section: Discussionmentioning
confidence: 55%
“…They are not widely recognized as possible adverse reactions of AstraZeneca COVID-19 vaccine, though the incidence of suspected myocarditis–pericarditis following mRNA and AstraZeneca COVID-19 vaccine from the vaccine adverse event reporting system was similar (1.6–5.0 versus 2.0–3.7 per million doses, respectively) [ 6 ]. To date, only a few cases of myocarditis following exposure to the AstraZeneca COVID-19 vaccine have been published [ 7 , 8 ]. Our patient age was not common for mRNA-induced myocarditis, but the typical age of AstraZeneca COVID-19 vaccine-related myocarditis has not previously been concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine-related myocarditis usually presented with mild symptoms, which resolved spontaneously with conservative treatment [ 7 , 9 ]. A severe form presented with cardiogenic shock and need for hemodynamic support had been scarcely reported [ 8 , 10 ]. Chest pain is the most common presentation; unlike other reports, our case presented with palpitation, which could be a manifestation of myocarditis, thyroiditis, or both [ 9 ].…”
Section: Discussionmentioning
confidence: 99%